2015
DOI: 10.1007/s00262-015-1686-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum osteopontin level and gene polymorphism as biomarkers: analyses from the Nordic Adjuvant Interferon alpha Melanoma trial

Abstract: Malignant melanoma is highly aggressive cancer with poor prognosis and few therapeutic options. Interferon alpha (IFN-α) has been tested as adjuvant immunotherapy in high-risk melanoma patients in a number of studies, but its beneficial role is controversial. Although IFN-α treatment can prolong relapse-free survival, the effect on overall survival is not significant. However, a small subset of patients benefits from the treatment, signifying the need for biomarkers able to identify a responding subgroup. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Finally, we found no association between the rs1126772, rs11730582, and rs4754 SNPs, as well as their haplotypes and pretreatment circulating OPN levels in our NSCLC cohort. Similar results were previously obtained by several other authors in lung cancer and melanoma patients [9,10,61]. However, rs11730582 in the promoter region was shown to be linked to serum/plasma OPN levels in nasopharyngeal and breast cancers [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we found no association between the rs1126772, rs11730582, and rs4754 SNPs, as well as their haplotypes and pretreatment circulating OPN levels in our NSCLC cohort. Similar results were previously obtained by several other authors in lung cancer and melanoma patients [9,10,61]. However, rs11730582 in the promoter region was shown to be linked to serum/plasma OPN levels in nasopharyngeal and breast cancers [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…Interferon-α stimulated anti-melanoma cytotoxic T lymphocytes by increasing the Th1 response rate, while OPN affects Th1 cells by increasing IFN-α production. In the IFN melanoma study, although the survival of the cases with a high level of OPN and receiving interferon treatment was better, no statistical significance could be demonstrated [18].…”
Section: Resultsmentioning
confidence: 93%
“…In addition, transcriptomic analyses have revealed that OPN is one of the most highly upregulated proteins in metastatic melanoma compared to benign nevi [ 67 ]. Furthermore, the levels of OPN are also elevated in the blood of melanoma patients compared to healthy controls [ 46 , 47 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…One report found a correlation between high OPN expression in tumours and increased risk of lymph node metastasis, as well as a marginal decrease in survival, which is closely linked to distant metastasis formation [ 71 ]. By contrast, a separate study found no correlation between OPN expression and overall or recurrence-free survival in melanoma patients [ 68 ].…”
Section: Discussionmentioning
confidence: 99%